(3JNWjW h JfXje HQGeL h MedGJ GdYdGbGJ GdYGeIs - (3HTjQ(B, (3GdYdGbs ((3YeGf(B:s (3OGQ GdjGRhQj(B,s, 2009)
(3eONd Gdi GdYdGbGJ GdYGeI , eaghe GdJNWjW h BdjGJg h CHYGOg aj eLGd GdGOGQI h GdYdGbGJ GdYGeI , JNWjW HQGeL GdYdGbGJ GdYGeI h MeGjJgG , JfXje HQGeL GdYdGbGJ GdYGeI h MedGJgG eY hLhOCSFdI ddefGbTI aj fgGjI cd aUds
(3eQGLY U(B.197s
Keywords: (3GdGYdGes; (3GdYdGbGJ GdYGeIs